1988
DOI: 10.1254/jjp.48.263
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Antinociception Induced by Noncatecholic Phenylethylamine Derivatives: The Relation of Endogenous Norepinephrine to Phenylethylamine Analog-Induced Antinociception

Abstract: Abstract-Characteristicsof the antinociceptive action of phenylethylamine deriva tives, amphetamine, 3-phenylethylamine (PEA) and 8-hydroxyphenylethylamine (OHPEA), were examined.The pain threshold of mice was measured by using the hot plate method.Intraperitoneal administration of a-methyl-p-tyrosine inhibited antinociception induced by PEA and OHPEA, and intracisternal administration of norepinephrine increased antinociception induced by PEA and OHPEA. Intra cisternal administration of phentolamine inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…PEA decreased norepinephrine in the brain and tended to increase the norepinephrine metabolite normetanephrine 15 minutes after administration, indicating a release of norepinephrine in the central nervous system, inducing antinociception. 19 To evaluate the hypothesis that norepinephrine is involved in mediating peripheral cannabinoid antinociception in our model, we studied this effect in rats treated with guanethidine, a depletor of peripheral sympathomimetic amines, 28 and the norepinephrine reuptake inhibitor, reboxetine. 67 Without the presence of norepinephrine, guanethidine induced an approximately 70% reversal of the peripheral effect of anandamide and PEA.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
See 2 more Smart Citations
“…PEA decreased norepinephrine in the brain and tended to increase the norepinephrine metabolite normetanephrine 15 minutes after administration, indicating a release of norepinephrine in the central nervous system, inducing antinociception. 19 To evaluate the hypothesis that norepinephrine is involved in mediating peripheral cannabinoid antinociception in our model, we studied this effect in rats treated with guanethidine, a depletor of peripheral sympathomimetic amines, 28 and the norepinephrine reuptake inhibitor, reboxetine. 67 Without the presence of norepinephrine, guanethidine induced an approximately 70% reversal of the peripheral effect of anandamide and PEA.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…18 Three lines of evidence suggesting an antinociceptive interaction between the adrenergic and the cannabinoid systems have also been proposed. [19][20][21] First, both α 2 adrenoceptor and cannabinoid receptors induce antinociception through inhibition of postsynaptic membrane excitation, Ca 2+ -inducing neurotransmitter release, [22][23][24] and the opening of adenosine triphosphate-sensitive K + channels. 7,25 Second, some cannabinoid receptor agonists, such as N-palmitoylethanolamine (PEA), release norepinephrine in the central nervous system, inducing antinociception.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amphetamine, one of the noncatecholic phenylethylamine derivatives, produces a slight but significant antinociceptive action (5). We (6,7) have also reported that PEA derivatives such as PEA, OHPEA and amphetamine have antinociceptive action which may involve endogenous serotonin, norepineph rine and opioid peptides.…”
mentioning
confidence: 94%